2005
DOI: 10.1002/art.21139
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss reduces knee‐joint loads in overweight and obese older adults with knee osteoarthritis

Abstract: Objective. To determine the relationship between change in body mass and knee-joint moments and forces during walking in overweight and obese older adults with knee osteoarthritis (OA) following an 18-month clinical trial of diet and exercise.Methods. Data were obtained from 142 sedentary, overweight, and obese older adults with self-reported disability and radiographic evidence of knee OA who underwent 3-dimensional gait analysis. Gait kinetic outcome variables included peak knee-joint forces and peak interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
325
2
8

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 456 publications
(353 citation statements)
references
References 29 publications
18
325
2
8
Order By: Relevance
“…Persons who are overweight with varus alignment will benefit greater owing to the interaction between alignment and body mass on dynamic knee joint loading with the association between alignment and load highest in patients with the highest mass [17,19]. One study reported that a reduction in body weight of 1 kg (10 N) was associated with a 1% reduction (0.496 Nm) in knee adduction moment [17]. In comparison with our results, in which we observed a reduction of 4% of peak knee adduction moment in the insole group, weight reduction should be highly effective.…”
Section: Discussionmentioning
confidence: 99%
“…Persons who are overweight with varus alignment will benefit greater owing to the interaction between alignment and body mass on dynamic knee joint loading with the association between alignment and load highest in patients with the highest mass [17,19]. One study reported that a reduction in body weight of 1 kg (10 N) was associated with a 1% reduction (0.496 Nm) in knee adduction moment [17]. In comparison with our results, in which we observed a reduction of 4% of peak knee adduction moment in the insole group, weight reduction should be highly effective.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these findings, it is meaningful to examine whether weight loss might prevent OA or delay its progression. Messier et al (39) indicated that each pound ( , 0?5 kg) of weight loss will result in a fourfold reduction in the load exerted on the knee per step during daily activities. Zamboni et al (38) also suggested that even small amounts of weight loss might be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…59 A subset of the ADAPT study cohort underwent biomechanical analysis testing over an 18-month period. 60 There was a significant relationship between weight loss and reduction in compressive knee-joint loads, with a four-pound reduction in knee-joint load per step for every 1 pound weight loss. To date, there are no longitudinal studies evaluating if weight loss slows the progression of knee OA but this effect would appear to be clinically plausible.…”
Section: Weight Reductionmentioning
confidence: 92%